2004
DOI: 10.1007/s00276-004-0258-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the presacral venous plexus: implications for rectal surgery

Abstract: The presacral venous plexus results from anastomoses between the lateral and median sacral veins, and courses into the pelvic fascia covering the anterior aspect of the body of the sacrum. The presacral venous plexus is not directly visible during rectal surgery, and injuries to this plexus may be life-threatening. Dissection of the retrorectal plane or anchoring of the rectum to the sacral promontory as in rectal prolapse surgery exposes the patient to the risk of injury to the presacral venous plexus. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 9 publications
0
26
0
4
Order By: Relevance
“…Eine Perforation der ventralen Sakrumkortikalis kann zu Verletzungen der Vasa iliaca communia und des präsakralen Venenplexus führen [1]. tomically, a relatively high position of the sacral wing in relation to the iliac crest is found, as well as the presence of mammillary processes and joint connections between lumbar and sacral transverse processes [45].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Eine Perforation der ventralen Sakrumkortikalis kann zu Verletzungen der Vasa iliaca communia und des präsakralen Venenplexus führen [1]. tomically, a relatively high position of the sacral wing in relation to the iliac crest is found, as well as the presence of mammillary processes and joint connections between lumbar and sacral transverse processes [45].…”
Section: Figurementioning
confidence: 99%
“…If the anterior sacral cortex is perforated, this may cause damage to the common iliac vessel and the presacral venous plexus [1].…”
Section: Instrumentarium Und Implantatementioning
confidence: 99%
“…As with GCTs in other locations, the treatment of choice is function-preserving surgery [5]. While complete surgical excision is considered to be the most efficient treatment, it is technically demanding and can result in substantial functional deficits [7][8][9] and even death.…”
Section: Introductionmentioning
confidence: 99%
“…13 The most likely area of injury is the lower sacrum, where Waldeyer's fascia is thick and may attach directly to the presacral fascia. As this entire pelvic venous system lacks valves, 15 it has been estimated that with the patient in the lithotomy position, the hydrostatic pressure in the presacral space is up to three times that of the inferior vena cava. 16 Experimental studies have demonstrated that blood loss from presacral veins measuring 2-4mm in diameter can reach up to 1,000ml/min and increasing the diameter of the vein by just 1mm can increase the blood loss almost threefold.…”
Section: 9mentioning
confidence: 99%